Pengalaman Penderita Hipertensi Dalam Penggunaan Tanaman Obat: Studi Fenomenologi - Layal, Kamalia; Salmi, Salmi (REAL in Nursing Journal, 2022)
AbstractHypertension is a degenerative disease and can cause various cardiovascular diseases such as stroke and heart failure which leads to morbidity and mortality.The treatment of hypertension takes a long time, one of the treatments that can help to manage hypertension is complementary alternative therapy using medicinal plants. The aim of this study was to explore the experience of hypertension sufferers in using medicinal plants. The design of this research is qualitative with a phenomenological approach. The participants in this study were 10 patients with hypertension who were diagnosed by a doctor and had used medicinal plants. Data were collected through in-depth interviews and field notes. Data analysis used an interpretive phenomenology approach of Diekelmann, Allen, & Tanner (1989). Four main themes were found: (1) beliefs in medicinal plants; (2) effectiveness and evidence of medicinal plants; (3) utilization of medicinal plants; (4) the supporting and obstacle factors to medicinal plants use. Furthermore, this research can be used as the basic for the furthere research in developing herbal based antihypertensive.Keywords: hypertension, medicinal plants, complementary alternative medicine.